Nanoscale Metal Particles as Nanocarriers in Targeted Drug Delivery System - Nurul Akmal, Che Lah; Samykano, Mahendran; Trigueros, Sonia (MedCrave, 2016)
In the recent years, noble metal particles such as gold (Au) and silver (Ag) have been used progressively as efficient and safe nanoscale drug carriers in treating malignant as cites of cancerous cells. These single crystal structures of functionalised thearapeutic particles with the size less than 100 nm in diameter had proven offered an excellent function to modulate the oxidative stress and toxicity at affected membrane cells particularly to achieve the site-specific delivery of drugs. This mini-review will highlight the current advances of Au and Ag nanoscale particles as smart chemotherapeutic molecule carriers to these malignancies in impeding cancer cell activities locally. The paper also reviewed valuable insights of their efficacy in maintaining and precisely control the drugs release level within the therapeutic windows.